1998
DOI: 10.1038/sj.jhh.1000577
|View full text |Cite
|
Sign up to set email alerts
|

Variability in vascular responsiveness between Mexican–Americans and White Americans

Abstract: Ethnic differences in vascular adrenergic responsiveness have been implicated to be a potentially important mechanism which may be responsible for some of the variations in haemodynamic patterns between races. These differences may account for the variability in the prevalence of hypertension in different groups. The main aim of this study was to determine whether there was a difference in venous responsiveness to the vasoactive agents, phenylephrine and isoproterenol, between Mexican-Americans and White Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…20 In a study among 24 white and black Americans, Eichler et al found a lower E max in African Americans compared to Caucasians and a lower ED 50 (245 and 342 ng/min for African Americans and Caucasians, respectively), although the latter was not statistically significant (P=0.50). 21 In contrast, in this present study, using a much larger cohort we found a similar, but statistically significant racial difference in ED 50 , and additionally a trend to increased E max in African Americans compared to Caucasians.…”
Section: Discussionmentioning
confidence: 92%
“…20 In a study among 24 white and black Americans, Eichler et al found a lower E max in African Americans compared to Caucasians and a lower ED 50 (245 and 342 ng/min for African Americans and Caucasians, respectively), although the latter was not statistically significant (P=0.50). 21 In contrast, in this present study, using a much larger cohort we found a similar, but statistically significant racial difference in ED 50 , and additionally a trend to increased E max in African Americans compared to Caucasians.…”
Section: Discussionmentioning
confidence: 92%
“…Luthra et al 16 reported very similar ED 50 values of norepinephrine in pairs of monozygotic twins that differed considerably in dizygotic twins. Eichler et al 17 and Dachmann et al 18 provided evidence that venous responses to α‐adrenoceptor agonists may be genetically determined.…”
Section: Discussionmentioning
confidence: 99%